Eettisten toimintapolitiikkojen kompleksisuus hallinnollisissa systeemeissä - Autioniemi, Jari; Demmke, Christoph (Hallinnon tutkimuksen seura, 2022)
The complexity of integrity policies in administrative systems According to the article, regulating administrative ethics is becoming increasingly complex. This article is based on a survey commissioned by the European Parliament on conflict of interest policies and their effectiveness in the EU Member States. The trends of administrative ethics are grounded on the growth of ethics bureaucracy, individualization of integrity policies – and broadening of the concepts such as conflict of interest. This kind of conceptualization indicates that unethical behaviour is linked to ever-widening areas of life, which in turn can complicate the design, implementation, and effectiveness of integrity policies. Also, systemic differences were found. The EU Member States, determined by a traditional bureaucratic system, regulate conflicts of interest through more detailed laws than the EU Member States whose systems are based more on managerial management practices. However, hybrid systems stand out as the most widely regulated.
Keywords: administrative ethics; conflict of interest; administrative systems; EU Member States; ethics reforms; fi=Julkisjohtaminen|en=Public Management|